EFFECT OF MARKET SHARE, LEVERAGE RATIO, AND CAPITAL INTENSITY RATIO ON PROFITABILITY IN MANUFACTURING COMPANY INDONESIA STOCK EXCHANGE - Kuncoro, Danu; one, Drs. Supardi, MM.; ekowati, SE., MM, Dhiana (Accounting, 2009)
The stock market is the investment vehicle for those who have surplus funds. Community to invest in the stock market with the aim of generating earnings or return on investment. Investment can be defined as an activity to place funds in one or more assets for a certain period in the hope to earn income and / or increase in value of investment. Purchase of shares in a company through capital market is one of the alternative forms of investment that many do when ini.Profitabilitas also be used to measure the company´s position in the competitive high industri.Semakin reflects the higher profitability of firms in the competitive market forces. In this regard, it should improve the profitability of such companies make a positive issue, improved management companies, so investors interested in investing in order to increase the capital and in turn has implications for corporate profitability naikknya. For investors, relating to market share, leverage ratio, the ratio of capital intensity, profitability can be used as a basis for making investment decisions because this ratio measures the company´s ability to produce levels of return on the investment made by the company. Keywords : market share, leverage ratio, the ratio of capital intensity, profitability